PENATAAN KELEMBAGAAN PEMERINTAH DESA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Rauf, Rahyunir (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
The issuance of Law No. 6 of 2014 About Village, for the third time village governed by a separate law, after the first time regulated by Law No. 19 of 1965 On Rural Township and second regulated by Law No. 5 of 1979 About the Village Government. This condition shows the village of serious attention of society, so that people feel the need to make updates. Because during this time the village setting incorporated into the Regional Government Law is considered still many weaknesses in governing the country and have not been able to accelerate the development of the village. Explanation of Law No. 6 of 2014, stated; "Village or called by any other name existed before the Homeland existing or formed. As evidence of the existence of the village, seen from the explanation of Article 18 UUD 1945, there are approximately 250 "Zelfbesturende landschappen", such as the Village in Java and Bali, Nagari in Minangkabau, and so forth ". The diversity of characteristics and the type of village, not a barrier for our founding fathers to make informed choices in a unitary state. Although we recognize the need there is homogeneity of the unitary state, but Homeland still provide recognition, protection and guarantee of the existence of a unit of community and unity of indigenous communities and their traditional rights are to grow and develop. The existence of Law No. 6 of 2014 set and answer the problems of the village administration that are expected to accelerate the development of the village, the village government through institutional arrangement.